Pemberdayaan Komunitas Adat Terpencil Suku Anak Dalam Melalui Program Pendidikan - Eka Nurwahyuliningsih; Soni Akhmad Nulhaqim; Hadiyanto Abdul Rachim (Universitas Padjadjaran, 2022)
Indigenous community with residential locations that are quite far from reach make it difficult to access educational services that have been provided by the government. The need for education for remote community is something that needs to be pursued, considering the right to education for all citizens. Education plays a very important role in helping remote indigenous community understand life's problems, are able to think independently, create business opportunities and are sensitive to the times. It can be seen clearly that in remote indigenous community the critical ability of indigenous community is still weak, even the number of educated indigenous community is still lacking. Based on the 2013 BAPPENAS, it is stated that some of the indigenous peoples hope that education can be used to defend themselves and deal with outsiders without loss. This article discusses an approach used in empowering community to achieve a good standard of living. This study is based on a literature study by examining several credible reference sources consisting of news articles, the latest scientific articles and books that are relevant to the topic of discussion. This article focuses on the importance of education for indigenous community, empowerment through an educational approach is one of the provisions obtained by indigenous community in adapting to current changes and facing the challenges of this modern era. Komunitas adat dengan lokasi tempat tinggal yang cukup jauh dari jangkauan menyebabkan sulit mengakses layanan pendidikan yang telah disediakan oleh pemerintah. Kebutuhan pendidikan bagi komunitas adat terpencil menjadi hal yang perlu diupayakan, hal ini mengingat adanya hak atas pendidikan bagi semua warga negara. Pendidikan sangat berperan untuk membantu komunitas adat terpencil dalam memahami persoalan hidup, mampu berpikir mandiri, kreatif menciptakan peluang usaha dan peka terhadap tuntutan zaman. Dengan kasatmata dapat dilihat bahwa di lingkungan permukiman komunitas adat terpencil kemampuan kritis komunitas adat masih lemah bahkan jumlah kaum terdidik dikalangan komunitas adat masih kurang. Berdasarkan publikasi Bappenas tahun 2013, disebutkan bahwa beberapa dari masyarakat adat mengharapkan pendidikan dapat digunakan untuk mempertahankan diri dan berhadapan dengan orang luar tanpa dirugikan. Artikel ini membahas pendidikan sebagai suatu pendekatan yang digunakan dalam memberdayakan komunitas adat agar dapat mencapai taraf hidup yang baik. Kajian ini didasarkan pada studi literatur dengan menelaah beberapa sumber referensi yang kredibel terdiri dari artikel berita, artikel ilmiah terbaru dan buku yang sesuai dengan topik pembahasan. Artikel ini menitikberatkan pada pentingnya pendidikan bagi komunitas adat, pemberdayaan melalui pendekatan pendidikan menjadi salah satu bekal yang diperoleh komunitas adat dalam menyesuaikan diri dengan perubahan saat ini serta menghadapi tantangan zaman modern ini.